1984
DOI: 10.1159/000225784
|View full text |Cite
|
Sign up to set email alerts
|

Renal Cell Carcinoma – Xenotransplantation into Immunosuppressed Mice

Abstract: 21 human renal cell carcinomas (RCC) were xenotransplanted into artificially immunosuppressed mice. 4 tumors grew successfully retaining some characteristics of the primary tumors (according to morphology and karyotype analysis), but losing metastatic capacity. One of the serially transplantable tumors (HT 40) with hyperdiploid cellular DNA content and estrogen receptor positivity failed to respond to the single maximally tolerated dose of several cytotoxic agents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1985
1985
2016
2016

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…83 PDTX models of RCC have been used for decades and may provide several advantages over cell line xenografts. 8085 RCC cells continuously cultured in vitro are known to acquire many genetic alterations not found in the original tumour. 86 In addition, the limited number of RCC cell lines available means that they lack the heterogeneity that characterizes kidney cancer in the human population.…”
Section: Renal Cell Carcinomamentioning
confidence: 99%
See 1 more Smart Citation
“…83 PDTX models of RCC have been used for decades and may provide several advantages over cell line xenografts. 8085 RCC cells continuously cultured in vitro are known to acquire many genetic alterations not found in the original tumour. 86 In addition, the limited number of RCC cell lines available means that they lack the heterogeneity that characterizes kidney cancer in the human population.…”
Section: Renal Cell Carcinomamentioning
confidence: 99%
“…18,87 Several studies have demonstrated that RCC PDTX models are similar to parental tumours as assessed by histology, karyotype, DNA-ploidy, and molecular cytogenetic analyses. 8085,88 Grisanzio et al 80 have also created orthotopic PDTX that exhibit high levels of histological, immunophenotypical and genetic concordance between the PDTX and the corresponding primary tumour. Another advantage of an RCC PDTX model is the ability to evaluate tumour angiogenesis, and studies have demonstrated that the vasculature of RCC PDTX are predominantly comprised of human endothelial cells, up to 35 days after implantation.…”
Section: Renal Cell Carcinomamentioning
confidence: 99%
“…Second, RCC is seldom treated with chemotherapy, and thus, the molecular genetics and behavior of the tumor is unlikely to be affected by previous exposure to DNA damaging agents. Third, RCCs implanted in mice preserve the histology and karyotype of patient tumors (10)(11)(12)(13)(14)(15)(16). Fourth, the implantation of tumors heterotopically in mice may affect tumor biology (17)(18)(19), but the site for orthotopic implantation of RCC, under the kidney capsule, is a privileged site for tumor growth (4).…”
Section: Introductionmentioning
confidence: 99%
“…The sensitivity of this embryonal carcinoma line to chemotherapy was much higher than that of other tumor types (colorectal carcinoma, renal cell car cinoma [6,11]). Similar conclusions were drawn by Steel et al [8] who compared the chemotherapeutic response of 6 tumor types (testicular teratoma, small cell and non-small cell lung carcinoma, breast car cinoma, colorectal carcinoma, melanoma) growing as xenografts in immunosuppressed mice.…”
Section: Lapis Kopper Bodrogi Sugar Lapis Eckhardtmentioning
confidence: 72%